Altered tissue factor activity and disrupted oxidant-antioxidant status in saliva of patients with oral lichen planus - Cansız, Derya; Beler, Merih; Ünal, İsmail; Eğilmezer, Gizem; Mızrak, Zülal; Emekli Alturfan, Ebru (My University, 2024)
Objective: The aim of our study was to investigate salivary tissue factor (TF) activity and oxidant-antioxidant status, which is an important defense system, in saliva samples collected from patients with oral lichen planus (OLP), and to determine the relationship between the antioxidant system and TF activity in OLP. Materials and Methods: Saliva samples were collected from patients with OLP (n=20) and healthy subjects (n=13). TF activity, lipid peroxidation (LPO), nitric oxide (NO), glutathione (GSH) levels, glutathione S-transferase (GST), and superoxide dismutase (SOD) activities were measured. Results: NO levels and GST activities were increased, whereas GSH levels and SOD activities were decreased, when compared with healthy subjects in the saliva samples collected from patients with OLP. In addition, TF activity was increased in the OLP group compared with the control group Conclusion: The results revealed that the salivary oxidant-antioxidant balance was disrupted in parallel with the increase in TF activity in patients with OLP.
Keywords: Oral Lichen Planus; Oxidative Stress; Saliva; Tissue Factor